Granulomatosis with polyangiitis in a patient treated with dabrafenib and trametinib for BRAF V600E positive lung adenocarcinoma - Dimou, Anastasios (BMC Cancer, 2020)
BACKGROUND: Dabrafenib and trametinib combination therapy is approved for the treatment of patients with BRAF V600E positive tumors including melanoma and lung cancer. The effect of BRAF and MEK inhibitors on the immune system is not fully understood although a number of case reports indicate autoimmune side effects related to the use of these drugs. Here, we discuss a case of a patient diagnosed with granulomatosis with polyangiitis (GPA) shortly after starting treatment with dabrafenib and trametinib for BRAF V600E positive metastatic lung adenocarcinoma. CASE PRESENTATION: A 57 years old female patient was diagnosed with recurrent lung adenocarcinoma following initial lobectomy for early stage disease. A BRAF V600E mutation was identified at the time of recurrence and she received combination dabrafenib and trametinib therapy. Shortly after commencement of treatment, she developed persistent fevers necessitating withholding both drugs. Pyrexia continued and was followed by left vision loss and acute kidney injury. Further rheumatological workup led to the unifying diagnosis of GPA. The patient was then treated with rituximab for GPA to the present date while all antineoplastic drugs were held. Lung cancer oligoprogression was addressed with radiation therapy and has not required further systemic treatment whereas GPA has been controlled to-date with rituximab. CONCLUSIONS: This case report raises awareness among clinicians treating patients with lung cancer for the possibility of triggering a flare of autoimmune diseases like GPA in patients with BRAF V600E positive lung cancer receiving treatment with BRAF directed therapy.